Understanding the link between ALDH2 genotypes and diabetes - Peng, Miaomiao; Liu, Ruikang; Zhang, Jiaoyue; Kong, Wen; Zheng, Juan; Hu, Xiang; Wan, Limin; Hu, Shengqing; Tian, Shenghua; Wang, Ying; Liu, Geng; Qiu, Kangli; et al. (Frontiers in Endocrinology, 2025)
IntroductionThe association between aldehyde dehydrogenase-2 (ALDH2) rs671 and diabetes remains controversial, with uncertainty about whether alcohol consumption or other factors mediate or modify this relationship. This study aimed to examine the ALDH2–diabetes association using standardized clinical criteria while systematically investigating potential confounding, mediating, and interacting factors in a community-based cohort.MethodWe analyzed baseline data from 4,535 participants in the China Cardiometabolic Disease and Cancer Cohort Study (4C study). Diabetes was diagnosed based on standardized clinical criteria, including fasting plasma glucose, 2-h postprandial glucose, glycosylated hemoglobin A1c (HbA1c), or documented prior diagnosis. We evaluated the association between ALDH2 rs671 and diabetes risk using both logistic and Cox regression models, with age as the time scale and adjustment for potential confounders. Comprehensive mediation and interaction analyses were performed to elucidate the underlying mechanisms.ResultAmong male participants, the ALDH2 rs671 GA/AA genotype was associated with a lower diabetes risk compared to the GG genotype after adjusting for alcohol consumption and other potential confounders (OR = 0.751, 95% CI: 0.567–0.995). Subgroup analyses revealed that this protective effect was most pronounced in individuals with BMI < 24 (OR = 0.651, 95% CI: 0.448–0.947), with significant interaction p-values of 0.024. In mediation analysis, abdominal adiposity accounted for 30.4% (95% CI: 10.0%–127.0%) of the ALDH2–diabetes association and BMI mediated 18.9% (95% CI: 4.8%–75.4%) of this relationship, while alcohol consumption showed no significant mediating effect (p = 0.56).ConclusionOur findings revealed that East Asian men with the ALDH2 GG genotype had an increased risk of diabetes compared to those with the GA/AA genotype, particularly among individuals with a BMI < 24. Interestingly, increased adiposity, especially abdominal fat, emerged as a potential mediator rather than alcohol consumption. Thus, individuals with the GG genotype, even with a relatively normal BMI, may benefit from regular moderate-intensity exercise and dietary interventions aimed at managing waist circumference.